Reoperation and revision rates at ten years after 1, 312 cemented Thompson's hemiarthroplasties: any need to change to a different implant?. (5th September 2022) - Khan, Sameer K.; Tyas, Ben; Shenfine, Amy; Jameson, Simon S.; Inman, Dominic S.; Muller, Scott D.; Reed, Mike R.
Abstract : Aims: Despite multiple trials and case series on hip hemiarthroplasty designs, guidance is still lacking on which implant to use. One particularly deficient area is long-term outcomes. We present over 1, 000 consecutive cemented Thompson's hemiarthroplasties over a ten-year period, recording all accessible patient and implant outcomes. Methods: Patient identifiers for a consecutive cohort treated between 1 January 2003 and 31 December 2011 were linked to radiographs, surgical notes, clinic letters, and mortality data from a national dataset. This allowed charting of their postoperative course, complications, readmissions, returns to theatre, revisions, and deaths. We also identified all postoperative attendances at the Emergency and Outpatient Departments, and recorded any subsequent skeletal injuries. Results: In total, 1, 312 Thompson's hemiarthroplasties were analyzed (mean age at surgery 82.8 years); 125 complications were recorded, necessitating 82 returns to theatre. These included 14 patients undergoing aspiration or manipulation under anaesthesia, 68 reoperations (5.2%) for debridement and implant retention (n = 12), haematoma evacuation (n = 2), open reduction for dislocation (n = 1), fixation of periprosthetic fracture (n = 5), and 48 revised stems (3.7%), for infection (n = 13), dislocation (n = 12), aseptic loosening (n = 9), persistent pain (n = 6), periprosthetic fracture (n = 4), acetabular erosion (n = 3), and metastatic bone disease (n = 1). Their status at ten years is summarized as follows: 1, 180 (89.9%) dead without revision, 34 (2.6%) dead having had revision, 84 (6.6%) alive with the stem unrevised, and 14 (1.1%) alive having had revision. Cumulative implant survivorship was 90.3% at ten years; patient survivorship was 7.4%. Conclusion: The Thompson's stem demonstrates very low rates of complications requiring reoperation and revision, up to ten years after the index procedure. Fewer than one in ten patients live for ten years after fracture. This study supports the use of a cemented Thompson's implant as a cost-effective option for frail hip fracture patients. Cite this article: Bone Jt Open  2022;3(9):710–715.